2007
DOI: 10.1149/1.2409059
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Height Enhancement of Al[sub x]Ga[sub 1−x]N∕GaN Schottky Diodes Prepared by P[sub 2]S[sub 5]∕(NH[sub 4])[sub 2]S Treatments

Abstract: The passivation of modulation-doped Al 0.1 Ga 0.9 N/GaN Schottky surfaces by treatment with ͑NH 4 ͒ 2 S and P 2 S 5 /͑NH 4 ͒ 2 S has been investigated. The current-voltage ͑I-V͒ curves of these Schottky diodes demonstrate that the Ti/Pt/Au-Al 0.1 Ga 0.9 N/GaN Schottky diodes prepared by P 2 S 5 /͑NH 4 ͒ 2 S treatment have the lowest reverse-leakage current ͑7.5 nA/cm 2 ͒ and the highest Schottkybarrier height ͑0.98 eV͒. Detailed X-ray photoelectron spectroscopy analysis indicates that a thin sulfide layer on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In Figure f, the 34.98 and 37.12 eV peaks can be attributed to W 4f 7/2 and W 4f 5/2 , respectively. Figure g demonstrates the binding energies of 132.5, 133.22, 133.55, and 134.2 eV corresponding to P 2p 3/2 , P 2p 1/2 , P–S, and P–O bonds, respectively, which are consistent with the P–O–P bond in Figure b. , In Figure h, the 225, 225.7, and 231.86 eV peaks can be attributed to S–S, Bi–S, and S–O bonds, respectively. , …”
Section: Resultssupporting
confidence: 64%
“…In Figure f, the 34.98 and 37.12 eV peaks can be attributed to W 4f 7/2 and W 4f 5/2 , respectively. Figure g demonstrates the binding energies of 132.5, 133.22, 133.55, and 134.2 eV corresponding to P 2p 3/2 , P 2p 1/2 , P–S, and P–O bonds, respectively, which are consistent with the P–O–P bond in Figure b. , In Figure h, the 225, 225.7, and 231.86 eV peaks can be attributed to S–S, Bi–S, and S–O bonds, respectively. , …”
Section: Resultssupporting
confidence: 64%
“…The information is gathered by "feeling" the surface with a mechanical probe. Piezoelectric elements that facilitate tiny but accurate and precise movements on (electronic) command enable very precise scanning [11]. Figure 5(a) and Figure 5(b) show the 2D and 3D images of the surface roughness on the AlGaN/GaN surface with different treatments, as measured using a Park Systems XE-70.…”
Section: Experimental Results For the Devicementioning
confidence: 99%
“…Pretreatment before the deposition of the passivating layer between the source, the drain, and the gate terminals is dominated by the effect of surface traps, which cause flicker noise and current collapse problems. For example, (NH 4 ) 2 S X sulfide treatment is known to eliminate native Ga 2 O 3 and As 2 O 3 dangling bonds on GaAs-and InP-related semiconductors, because of the formation of stable Ga-S and As-S bonds during immersion [10,11]. In this work, a P 2 S 5 /(NH 4 ) 2 S X + UV treatment that suppresses surface traps is studied.…”
Section: Introductionmentioning
confidence: 99%
“…In literatures, many researchers reported sulfur treatment with the solutions of (NH 4 ) 2 S and P 2 S 5 /(NH 4 ) 2 S is well known to form thin sulfide layers on GaAs-or InP-related semiconductors [1], [2]. Additionally, Chang et al reported that treating Schottky contacts formed on AlGaN/GaN heterostructures with P 2 S 5 /(NH 4 ) 2 S solution could maximize the Schottky barrier height (SBH) and have the lowest reverse-leakage current [3]. This proves that P 2 S 5 /(NH 4 ) 2 S treatment is an effective method in the passivation of GaN surface.…”
Section: Introductionmentioning
confidence: 99%